2010
DOI: 10.1353/hpu.0.0314
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Medication Cost-Related Non-adherence among Medicare CAHPS Respondents: Disparity by Hispanic Ethnicity

Abstract: Hispanic ethnicity was significantly associated with CRN. More research is needed to understand interventions to eliminate the disparity for this minority group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 114 publications
2
14
0
Order By: Relevance
“…Also, our findings on the racial disparity in CRN between NH black and NH white were consistent with previous studies [36,38,39]. While our study did not indicate a significance gap in CRN between Hispanics and NH white, Frankenfield et al (2010) [40] found a higher prevalence of CRN among Hispanic Medicare enrollees compared to non-Hispanics. Our findings along with these previous studies suggest that social support and fiscal policies should be promoted to reduce the disparities and help these vulnerable populations avert CRN.…”
Section: Discussionsupporting
confidence: 92%
“…Also, our findings on the racial disparity in CRN between NH black and NH white were consistent with previous studies [36,38,39]. While our study did not indicate a significance gap in CRN between Hispanics and NH white, Frankenfield et al (2010) [40] found a higher prevalence of CRN among Hispanic Medicare enrollees compared to non-Hispanics. Our findings along with these previous studies suggest that social support and fiscal policies should be promoted to reduce the disparities and help these vulnerable populations avert CRN.…”
Section: Discussionsupporting
confidence: 92%
“…Our study supports other groups that have presented data on how people of lower socioeconomic status and ethnic minorities report higher rates of cost-related medication nonadherence 37,47,5257…”
Section: Discussionsupporting
confidence: 91%
“…Because we used subjective, retrospective measures of adherence that are prone to biases such as social desirability or memory effects and chose a liberal cut-off, the actual nonadherence rates might be even higher than presented here. This is rather surprising considering that one of the main barriers to adherence, out-of-pocket costs for medication [5], [20] is unlikely an influential factor of nonadherence in Germany. Most of the patients in Germany have health plans with no or only marginal cost sharing for medication.…”
Section: Discussionmentioning
confidence: 98%